2021
DOI: 10.1111/acel.13419
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in mitochondrial dynamics with age‐related Sirtuin1/Sirtuin3 deficiency impair cardiomyocyte contractility

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…Western blot analysis and co‐immunoprecipitation (co‐IP) were performed following previous description with some modification (Bourdenx et al, 2021; Shen et al, 2021; Zhang et al, 2021). We performed plasma membrane protein isolation according to the directions provided by Minute™ Plasma Membrane Protein Isolation and Cell Fractionation Kit (Invent Biotechnologies, catalog number: SM‐005).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis and co‐immunoprecipitation (co‐IP) were performed following previous description with some modification (Bourdenx et al, 2021; Shen et al, 2021; Zhang et al, 2021). We performed plasma membrane protein isolation according to the directions provided by Minute™ Plasma Membrane Protein Isolation and Cell Fractionation Kit (Invent Biotechnologies, catalog number: SM‐005).…”
Section: Methodsmentioning
confidence: 99%
“…[ 35 ] For example, age‐related deficiency of SIRT3 in heart was proven to affect mitochondrial function, resulting in impaired contractile function of cardiomyocytes. [ 36 ] Here, we found that AR‐C17 could enhance SIRT3 expression in a dose‐dependent manner both in ApoE −/− mice and ox‐LDL‐treated HUVECs. Moreover, the protective effect of AR‐C17 on cells apoptosis, mitochondrial dynamic, and respiration function was depended on SIRT3, indicating it maybe a specific target signaling molecule of AR‐C17.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, the activation of SIRT1 and SIRT3 could activate the ATP production and the mitochondrial antioxidant function in skeletal muscle 37 . Furthermore, it was reported that SIRT1/SIRT3 deficiency resulted in impaired mitochondrial fusion and decreased mitochondrial perimeter in cardiomyocyte 38 . More importantly, as previously reported, the deficiency of SIRT1/3 have identified to promote the progression of PAH 17 , 18 .…”
Section: Discussionmentioning
confidence: 99%